THE LEGAL NATURE OF INTELLECTUAL RIGHTS. A PERSPECTIVE FROM THE CIVIL RIGHT - Flores Flores, Pavel (2019)
Intellectual property is a discipline that combines a series of legal institutions that are coordinated and adapted in the framework of its study, interpretation and application; even so, its legal nature is heterogeneous and not free from theoretical discussions and debates, which have an impact on its practical application. In this regard, we will study the legal relationship between the provisions contained in our Civil Code and the special legislation (D. Leg. 822 – D. Leg. 1075 - Decision 486) on intellectual property law, in such a way that we approach the generic application of the same institution, referring to intellectual rights. Thus, we reflect on both regulations and their possibility of interpretation and application, avoiding that the norm tends to vacuum, opacity and systemic incoherence. Our study is not only perceived from the theoretical foundations, but it is important in the development of our subject matter and its application in our legal reality